Improving Students Vocabulary Mastery through Guess My Move Game Gender-Based - Amalia, Arsyi Rizqia (LPPM Universitas Advent Indonesia, 2020)
In learning a language, vocabulary is the most important thing that should be mastered by learners. The English ability of primary school students is very closely related to the vocabulary mastery that they have. This research aims to find the answer to the following questions: 1) How is the application of Guess My Move Game model in learning English in primary grade school students? 2) How the students' English vocabulary mastery improve by using the Guess My Move Game model? and 3) Are there differences in the mastery of English vocabulary in male and female students using Guess My Move Game model? The research method was used in this study is Classroom Action Research with Kemmis and McTaggart design. The total population was 24 students of first primary school grade. The group was divided by gender. Based on the performance of group scores, it indicates that the female group gets the highest score, but the average highest score is achieved by the male groups. The result of this research shows that the Guess My Move Game learning model can improve students’ English vocabulary mastery both in individual and group scores.